A Mixed Infection of Helenium Virus S With Two Distinct Isolates of Butterbur Mosaic Virus, One of Which Has a Major Deletion in an Essential Gene - Hammond, John; Reinsel, Michael; Grinstead, Samuel; Lockhart, Ben; Jordan, Ramon; Mollov, Dimitre (Frontiers in Microbiology, 2020)
Multiple carlaviruses infect various ornamental plants, often having limited host ranges and causing minor symptoms, yet often reducing yield or quality. A mixed infection of butterbur mosaic virus (ButMV) and helenium virus S (HelVS) was identified from a plant of veronica (Veronica sp.) showing foliar mosaic and distortion. Carlavirus-like particles were observed by transmission electron microscopy (TEM), and RNA from partially purified virions was amplified by random RT-PCR, yielding clones of 439-1385 bp. Two partially overlapping clones including coat protein (CP) sequence, and two of four partial replicase clones, were closely related to ButMV-J (AB517596), previously reported only from butterbur (Petasites japonicus) in Japan. Two other partial replicase clones showed lower identity to multiple carlaviruses. Generic primers which amplify the 3’-terminal region of multiple carlaviruses yielded clones of three distinct sequences: 1) HelVS (98% identity); 2) ButMV-A (82% identity to ButMV-J); and 3) ButMV-B (78% identity to each of ButMV-J and ButMV-A). HelVS was previously reported only from Helenium hybrids and Impatiens holstii. Further amplification of upstream fragments revealed that ButMV-B had an internal deletion in TGB1, confirmed by amplification across the TGB1 region of both ButMV-A and ButMV-B using isolate-specific primers. Essentially the complete genomes of both ButMV-A and ButMV-B were obtained from high throughput sequencing (HTS), confirming the deletion within ButMV-B, which is presumably maintained through complementation by ButMV-A. An essentially complete HelVS genome was obtained by HTS from the same sample. Additional Veronica hybrids infected with HelVS were identified by TEM and RT-PCR, including cv. ‘Sunny Border Blue’ which was also subjected to HTS. This resulted in assembly of an 8,615 nt near complete HelVS genome, with high identity to that from the mixed infection. The predicted CP sequence has 96% amino acid (aa) identity to HelVS from helenium (Q00556). Other ORFs show a maximum of 54% (TGB3) to 68% (NABP) aa identity to the equivalent ORFs of other carlaviruses. These results demonstrate for the first time maintenance by complementation of a carlavirus isolate with a major deletion in an essential gene, and confirm that HelVS is a distinct species in the genus Carlavirus.